Advances in choroid-glaucoma structural-functional correlations using swept-source optical coherence tomography - Ying Tang; Yun Zhao; Qiyao Wang; Jia Li (Photodiagnosis and Photodynamic Therapy, 2025)
The choroid is a highly vascularized tissue that provides the main blood flow supply, mostly oxygen and nutrients, to the retina. The choroid is thought to play an important role in the progression of glaucoma because of its special structure and rich blood flow. However, the exact mechanism remains unclear due to limitations in research techniques. In this review, the pathophysiology of glaucoma is elucidated by combining swept-source optical coherence tomography (SS-OCT) results with noninvasive angiography data to comprehensively assess the anatomy and blood flow in the choroids of glaucoma patients. Our analyses suggest that functional and structural changes in the choroid are evident in glaucoma patients as the disease progresses and that the action mechanism varies across different types of glaucoma. This review highlights the potential of SS-OCT to improve the early diagnosis and monitoring of glaucoma. Understanding the role of the choroid in glaucoma may lead to the development of new therapeutic approaches and thus facilitate the early detection, diagnosis and treatment of glaucoma.